Cellular reprogramming with multigene activation by the delivery of CRISPR/dCas9 ribonucleoproteins via magnetic peptide-imprinted chitosan nanoparticles. (January 2021) - Lee, Mei-Hwa; Lin, Cheng-Chih; Thomas, James L.; Li, Jin-An; Lin, Hung-Yin
Abstract: Induced pluripotent stem cells are usually derived by reprogramming transcription factors (OSKM), such as octamer-binding transcription factor 4 (OCT4), (sex determining region Y)-box 2 (SOX2), Krüppel-like factor 4 (KLF4), and cellular proto-oncogene (c-Myc). However, the genomic integration of transcription factors risks the insertion of mutations into the genome of the target cells. Recently, the clustered regularly interspaced short palindromic repeat-associated protein 9 (CRISPR/Cas9) system has been used to edit genomes. In this work, dCas9-VPR (dCas9 with a gene activator, VP64-p65-Rta (VPR), fused to its c-terminus) and guide RNA (gRNA) combined to form ribonucleoproteins, which were immobilized on magnetic peptide-imprinted chitosan nanoparticles. These were then used to activate OSKM genes in human embryonic kidney (HEK) 293T cells. Four pairs of gRNAs were used for the binding site recognition to activate the OSKM genes. Transfected HEK293T cells were then prescreened for the high expression of OSKM proteins by immunohistochemistry images. The optimal gRNAs for OSKM expression were identified using quantitative real-time polymerase chain reaction and the staining of OSKM proteins. Finally, we found that the activated expression of one of the OSKM genes is up to three-fold higher than that of the other genes, enabling precise control of the cell differentiation. Graphical abstract: Image 1 Highlights: Molecularly imprinted polymer nanoparticles were used to deliver dCas9 ribonucleoproteins to activate OSKM genes. Two-guide RNAs for each OSKM gene were studied. Transfected HEK293T cells were then screened using immunohistochemistry. The optimal-guide RNAs for OSKM expression were also identified using qRT-PCR.